Dynamics of Reactive Oxygen Species on Cobalt-Containing Spinel Oxides in Cyclic CO Oxidation - Maik Dreyer (MDPI AG, 2021)
Reactive oxygen species (ROS) are considered to be responsible for the high catalytic activity of transition metal oxides like Co3-xFexO4 in oxidation reactions, but the detailed influences of catalyst composition and morphology on the formation of these reactive oxygen species are not fully understood. In the presented study, Co3O4 spinels of different mesostructures, i.e., particle size, crystallinity, and specific surface area, are characterized by powder X-ray diffraction, scanning electron microscopy, and physisorption. The materials were tested in CO oxidation performed in consecutive runs and compared to a Co3-xFexO4 composition series with a similar mesostructure to study the effects of catalyst morphology and composition on ROS formation. In the first run, the CO conversion was observed to be dominated by the exposed surface area for the pure Co-spinels, while a negative effect of Fe content in the spinels was seen. In the following oxidation run, a U-shaped conversion curve was observed for materials with high surface area, which indicated the in situ formation of ROS on those materials that were responsible for the new activity at low temperature. This activation was not stable at the higher reaction temperature but was confirmed after temperature-programmed oxidation (TPO). However, no activation after the first run was observed for low-surface-area and highly crystalline materials, and the lowest surface-area material was not even activated after TPO. Among the catalyst series studied here, a correlation of small particle size and large surface area with the ability for ROS formation is presented, and the benefit of a nanoscaled catalyst is discussed. Despite the generally negative effect of Fe, the highest relative activation was observed at intermediate Fe contents suggesting that Fe may be involved in ROS formation.